Field Evaluation of Ammonia Volatilisation Loss from Urea and its Control Using Urease Inhibitors and Soluble Salts - Pancras, Helen (1991)
Urea, when surface-applied to soils often resulted in high losses due to volatilisation of ammonia. This study was undertaken to measure ammonia volatilisation loss from urea on two soils under field conditions and to study the effect of urease inhibitors and soluble salts on ammonia volatilisation loss from urea. The N- 15 recovery technique was employed because it posed no disturbance to the field micro-environment. Experimental evidence showed that other pathways of nitrogen loss such as denitrification did not occur during the period of the experiment. Leaching losses were taken into account by sampling deeper in the soil profile until no further fertilizer nitrogen was recovered. There fore any N-15 lost from the soil profile was due to ammonia volatilisation process alone. Ammonia volatilisation loss was calculated by taking the. difference between the added and the recovered N-15.